"Forget it, let's go with a handshake": contracting practices of exporting small to medium size enterprises (SMEs). Issue 3 (22nd June 2021) - Kahiya, Eldrede T.; Butler, Petra
Abstract : Purpose: This paper aims to dissect cross-border contracting practices among exporting businesses. The under-representation of exporter-importer dynamics and the superficial understanding of contracts are the motivation for this exploratory study. Design/methodology/approach: The qualitative multiple case study design focuses on 18 small to medium size enterprise (SMEs) exporting from New Zealand. The analysis encompasses coding, pattern matching and explanation building. This paper uses coding to uncover themes and pattern matching/cross-case comparison to facilitate explanation building. Findings: The paper underlines the scant use of formal international sales/distribution contracts, the lack of knowledge concerning contracting, barriers to contract formation, misgivings about the court system and litigation and the adoption of proxy contracts. This paper depicts varieties of contracting practices, namely, no formal contract, improvisational, normative, and formal contractual arrangements and underlines the context in which each approach applies. Research limitations/implications: Similar to most studies in this area, the dissection of contracting practices derives from the exporter side of the dyad. This robs the research of a holistic view of the exchange. Nonetheless, this paper contributes to a better understanding of contract formation and formalization and to the role of context in shaping the activities of exporting SMEs. Practical implications: Although formal contracts are vital, they are not obligatory in all exchanges. Contracts matter more for high intensity exporters with comparatively short relationship histories, selling knowledge-intensive products in predominantly non-relational cultures. Policymakers should highlight the importance of contracts in such contexts and direct SMEs to several freely available resources on cross-border contracting. Social implications: The research casts fairness/equity and access to justice as pertinent structural disadvantages impacting the contracting practices of exporting SMEs. Originality/value: According to the authors' knowledge, this paper is among the first studies to provide an in-depth portrayal of the contracting practices of exporting SMEs, to detail the pervasiveness of non-contractual contracting practices and to depict contracting as nuanced and context-dependent.